Economic Behavior of Fisherfolks that Govern their Decisions to Practice Accounting: Evidence from Probit Models - Emmanuel Onsay; Kevin C. Baltar; Karlo Pedro L. Medroso II; Ivan Ruzzel C. Pesino (Journal of Mathematics Instruction, Social Research and Opinion, 2022)
The study reveals the economic behavior of fisherfolks that governs their decisions to practice accounting in Partido district, Camarines Sur, Philippines. Economic behavior was modeled and measured through the following parameters: the socioeconomic characteristics of the fisherfolks and their economic transactions; the economic perceptions on socioeconomic contribution, market sustainability, and financial viability of fishing activity; the recordkeeping practices they adopt and constraints they encounter; and the Willingness to participate in accounting enhancement programs. Nonlinear models were utilized, and a causal-explanatory design was applied. The survey was conducted throughout the four sectors of the district. Most fisherfolks are married men with an average age of 45. Most are elementary graduates, have 7-8 children, and are impoverished. They have been observing 6 recordkeeping practices and have asserted 14 types of constraints. They have identified 10 economic transactions that need a formal bookkeeping system and expressed 21 economic perceptions about the fishing industry. Based on probit models, 11 variables govern their decisions to practice accounting: 2 socioeconomic characteristics; 3 composite economic perceptions; 3 composite economic transactions; and 3 fishing activities as control variables. Finally, the study proposes policy interventions to improve the livelihood and uplift the accounting practices of fisherfolks.